Three-Dimensional Simulation of Robot Path and Heat Transfer of a TIG-Welded Part with Complex Geometry - Daneshjo, Naqibullah, 1964-
Princíp off-line programovania. Integrácia modelov prenosu tepla a off-line programovania.